Analisis Pengaruh Seo dan Iklan Online Terhadap Keputusan Pembelian Konsumen - Kerry, Winson John; Elisa, Lilis; Hoverio, Auron Rafael; Dalon, Dalon; Jaya, Oki (Universitas Internasional Batam, 2025)
The use of Search Engine Optimization (SEO) technology and online advertising as a marketing medium shows how marketing strategies have shifted in the digital era. Although both are widely used, the effectiveness of this strategy on purchasing decisions is not fully clear yet. This study tries to find out how much influence SEO and online advertising have on online purchasing decisions. The method used is a quantitative approach with a survey technique by distributing questionnaires to 400 students of Universitas Internasional Batam (UIB) class of 2023–2024. Data analysis was carried out using the Structural Equation Modeling (SEM) method using SmartPLS 3.2.9 software. The results of the study show that both SEO and online advertising have a real effect on online purchasing decisions. SEO contributes to increasing visibility and trust in a product, while online advertising helps catch the consumer attention and buying interest. Hopefully, this research can be a helpful guide for for business actors in developing effective digital marketing strategies, as well as increasing public understanding of the importance of the role of SEO and online advertising in influencing purchasing decisions in the digital era.